Alpentransit: BLS nimmt 2007 Lötschberg-Basistunnel in Betrieb. - Anreiter, Wilfried; Barth, Markus (Deutscher Verkehrs-Verlag, 2005)
Die BLS Lötschbergbahn AG (BLS) wird 2007 den ersten Alpen-Basistunnel durch den Lötschberg in Betrieb nehmen. Damit wird die Voraussetzung für eine wirkungsvolle Verkehrsverlagerung auf die Schiene geschaffen. Bau und Betriebsvorbereitung laufen derzeit auf Hochtouren. Eine Standortbestimmung. difu

In 2007 Switzerland's Lötschberg 'base tunnel' will be put into operation as the first such rail tunnel across the Alps. It will notably augment the freight transport capacity (especially for transit traffic) und reduce journey times of long distance passenger services. The 35 km long tunnel is conceived as a complex and multi-purpose facility that meets the most stringent safety requirements. As the future operator of this tunnel, the BLS Lötschbergbahn AG is actively engaged in preparations for this new task. Partly in conjunction with the SBB, the company is currently having the tunnel's access routes built, is acquiring the necessary rolling stock (fire fighting, emergency / rescue, construction / maintenance etc.) and is installing a special support and rescue centre. The company is also adjusting its organizational set-up and operational procedures to provide a suitable base for operators' optimal use of the rail tracks in line with demand. difu
Keywords: Verkehr; Schienenverkehr; Eisenbahntunnel; Kosten-Nutzen-Analyse; Wirtschaftlichkeit; Güterverkehr; Personenverkehr; Schnellverkehr; Finanzierung; Verkehrstechnik; Verkehrssicherheit; Inbetriebnahme; Transitverkehr; Betriebskonzept; Verkehrsverlagerung